RUP IN IT PROJECT MANAGEMENT (Research Bulletins of the Faculty of Economic Sciences, 2021)
This publication describes the best practice for IT Software Development Man-agement. The main purpose of this article is a presentation RUP practices as the method of managing IT software development and characterizing strong and weak sides.The Rational Unified Processis an iterative software development process framework created by the Rational Software Corporation. RUP is not a single concrete prescriptive process, but rather an adaptable process framework, intended to be tailored by the de-velopment organizations and software project teams that will select the elements of the process that are appropriate for their needs.